Three cases of photoallergic contact dermatitis induced by the ultraviolet absorber benzophenone that occurred after dermatitis due to ketoprofen‐Investigation of cosensitization with other ultraviolet absorbers and patient background. Issue 5 (21st August 2019) - Tanahashi, Tomoko; Sasaki, Kazumi; Numata, Mitsuru; Matsunaga, Kayoko
Abstract: Objectives: Three teenage patients developed dermatitis at the site of contact of a free‐pass wristband from an amusement park. Each had experienced dermatitis due to ketoprofen. A chemical analysis of the components of the wristband and patch testing determined that the cause of the dermatitis was benzophenone, and this reaction was considered to be due to the cross‐reaction of ketoprofen and benzophenone. Because those who are photosensitized to ketoprofen are often known to coreact with several ultraviolet absorbers, we investigated the presence of cosensitization to various ultraviolet absorbers in the three patients. We also wanted to explore the background of how photosensitization to ketoprofen can occur in such young individuals. Methods: The three patients underwent patch testing and photopatch testing with various ultraviolet absorbers. We also conducted a questionnaire survey of patients using ketoprofen‐containing topical medications. Results: Positive photoallergic reactions were observed only with benzophenone‐3, benzophenone‐4, and octocrylene. The frequency of positive reactions was higher than in previous studies of cases after ketoprofen sensitization. About half of patients using topical medications containing ketoprofen did not know that ketoprofen could cause photocontact dermatitis. Most patients did not know about the duration of avoidance of ultraviolet exposure. Conclusions: It is possible that photocontact allergy to substituted benzophenones and octocrylene was strongly established by being sensitized twice to ketoprofen and benzophenone. Sensitization to ketoprofen sometimes occurs at a young age, probably because of insufficient communication of the risk of photosensitization. Abstract : Three cases who developed photoallergic contact dermatitis induced by the ultraviolet absorber benzophenone that occurred after dermatitis due to ketoprofen were investigated for the presence of coreactions to various UV absorbers, and we explored how photosensitization to ketoprofen can occur in such young individuals by questionnaire survey of patients actually using ketoprofen‐containing external preparations.